Clinical Versatility of the Facility-Equator Implant System as Mandibular Overdenture Retainers - Anna Paula da Rosa Possebon; Alessandra Julie Schuster; Amália Machado Bielemann; Ana Paula Pinto Martins; Samille Biasi Miranda; Otacílio Luiz Chagas-Júnior; Luciana de Rezende Pinto; Fernanda Faot (Case Reports in Dentistry)
The use of mandibular overdentures (MO) for the rehabilitation of totally edentulous individuals with limited bone availability is widespread and has proven clinical success. Narrow diameter implants (NDI) are available on the market as MO retainers to solve problems related to limited bone availability and bone thickness, providing a low-cost, minimally invasive treatment option. This technique evolved over the years, and changes frequently involved the number of implants used as MO retainers, as the adoption of a smaller number of implants can generate biomechanical disadvantages, contributing to the increased stress in peri-implant tissues, which may accelerate marginal bone loss (MBL), in addition to reducing masticatory capacity and satisfaction with rehabilitation. Some studies pointed out that the use of 3 or more implants as MO retainers improves the biomechanics. Thus, the objective of this study was to report 3 different clinical cases where 3 or more NDI were adopted to retain mandibular overdentures in association with diverse loading protocols: (i) 3 implants adopting conventional loading, (ii) 4 implants using progressive loading, and (iii) 4 implants with hybrid loading. The case with 4 implants and progressive loading showed a slight worsening of masticatory function at 1 year, in addition to a more pronounced MBL compared to other cases, but with improvements in satisfaction and oral health-related quality of life. Thus, NDI can be used as MO retainers with predictability and clinical success, using different numbers of implants and loading protocols.